Implementasi Strategi Manajemen Sumber Daya Manusia Dalam Upaya Meningkatkan Mutu Pendididikan Islam (Studi Kasus di MI Darul Muta’allimin Patianrowo Nganjuk) - Ali Fauzi; Binti Maunah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
The most important part of an organization apart from technology and capital is human resources (HR). This is because humans themselves control other elements. This study aims to examine and determine the Implementation of the Human Resource Management Strategy at MI Darul Muta'allimin Patianrowo Nganjuk in an effort to improve the quality of education. This research is a non-statistical analytical descriptive research with a qualitative approach with a case study design. Information obtained through interviews, observations and documentation. Based on the research results, it can be explained that the Implementation of the Human Resource Management Strategy at MI Darul Muta'allimin Patianrowo Nganjuk in an effort to improve the quality of education has quite a positive effect on the achievements and vision and mission of the madrasa program. The positive influence is caused by several factors in the management of human resource management. However, there are also some inhibiting factors, but all of them are solvable.